2015
DOI: 10.20489/intjecse.31608
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Sound Field Amplification Systems for Language Development During Early School Years In Contexts Of Socio-Economic Exclusion: The Neglected Role Of Classroom Contextual Dimensions

Abstract: This study examined the efficacy of classroom sound field amplification system for the language development of children, aged 4-7, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The findings from this study supports other research indicating that sound amplification systems are related to a range of positive outcomes for children (Kazmierczak-Murray & Downes, 2015), particularly in the area of listening (Darai, 2000;Rosenberg et al, 1999).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings from this study supports other research indicating that sound amplification systems are related to a range of positive outcomes for children (Kazmierczak-Murray & Downes, 2015), particularly in the area of listening (Darai, 2000;Rosenberg et al, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…Research to date (Kazmierczak-Murray & Downes, 2015) suggests that sound amplification enhancements in classrooms result in a number of positive outcomes, including listening and learning behaviour in the classroom (Darai, 2000;Rosenberg et al, 1999), speech recognition (Bradley & Sato, 2008), on-task behaviour in the classroom (Eriks Brophy & Ayukawa, 2000) and a range of academic dimensions (Flexer, Kemp Biley, Hinkley, Harkema & Holcomb, 2002;Massie & Dillon, 2006). Other research has found improvements in speech perception (Mendel, Roberts & Walton, 2003), student attention and participation (Edwards & Feun, 2005), and phonemic awareness (Flexer et al, 2002).…”
Section: Sound Amplification Systemsmentioning
confidence: 99%
“…The benefits of SFA have been researched regarding effects on room acoustics with various populations. Numerous researchers have studied the benefit of using SFA systems to improve general listening conditions (e.g., Anderson & Goldstein, 2004; Crandell et al, 2001; Kazmierczak-Murray & Downes, 2015; Wilson et al, 2011). Research with amplification includes students with varying diagnoses such as those with Down syndrome (Bennetts & Flynn, 2002), emotional and behavioral disorders (EBDs; Maag & Anderson, 2006), and attention deficit hyperactivity disorder (ADHD; Maag & Anderson, 2007).…”
Section: Sound-field Amplification (Sfa)mentioning
confidence: 99%